Non-formal spaces in geography education: the importance of observatório astronômico antares in Feira de Santana /BA - dos Santos, Jonathas Jesus (Revista Ensino de Geografia (Recife), 2019)
The teaching of Geography, in non-formal spaces, allows an exit from the four walls of the classroom, favoring the desire to be at a distance with other possibilities of knowledge construction. In this sense, the general objective is how non-formal educational spaces are defended by secondary school teachers. Therefore, we used a qualitative approach for an investigation, with the case study of the Antares Astronomical Observatory in Feira de Santana-Ba. The instruments for data collection were viewed, questionnaires and interviews with teachers of Geography of basic education. Two thematic categories were elaborated: The first one, the relevance of the non-formal spaces of teaching: the discourse to the practice, reporting as contradictions the speeches andthe practices of the teachers of Geography, another one, on the use of the spaces nonforms in the Geography teaching. It was found that a large number of teachers are still available in the school environment, and sometimes the possibilities of a non-formal teaching space. However, many Geography teachers use the unformed spaces, although they are little informed about the non-institutionalized, for expository and dialogic classes, collaborating with meaningful learning and making even more sense for the students' world